Formulation and evaluation of orally disintegrating film (ODF) containing piperine-succinic acid cocrystal - Uswatul Hasanah; Lili Fitriani; Verlia Nisrina Putri; Erizal Zaini (Pharmaciana, 2023)
Piperine is a type of alkaloid found in plants of the Piperaceae family, including Piper nigrum and Piper longum, which has numerous pharmacological properties and is being developed as a nutraceutical. However, its poor solubility makes delivering in effective doses for therapeutic purposes challenging. To overcome this limitation, the cocrystals of piperine and succinic acid was prepared, which are more soluble, and then formulated into orally disintegrating films (ODFs) for better delivery. The cocrystals were formed using the slurry method, while the ODFs were made using the solvent-casting method with different concentrations of hydroxypropyl methylcellulose (HPMC) and polyethylene glycol (PEG) 400. The resulting films were evaluated for various parameters, such as their organoleptic characteristics, weight and thickness uniformity, pH, moisture content, swelling properties, and disintegration time. The results showed that the ODF with 6% HPMC as a film-forming polymer and 0.6% PEG 400 as a plasticizer loaded with 10 mg of piperine in the form of piperine-succinic acid cocrystal was the best formula. This ODF formulation disintegrated in less than one minute and was found to be a good film with uniform content.